Reduction in Healthcare Resource Utilization Following Treatment With a Home-Based Footworn Device in Patients With Knee Osteoarthritis: A Retrospective Claims Analysis - Josh Mark; Shirley Shema-Shiratzky; Joel Sommer; Tim Nolan; Ganit Segal (Journal of Health Economics and Outcomes Research)
# Background One in 7 US adults has knee osteoarthritis (OA) and almost two-thirds of them suffer from low back pain. OA is the third most rapidly rising condition associated with disability and leads to a significant burden on the healthcare system and society.